Procedures for reception of priest and deacon ordination - JAKUBIAK, TOMASZ (Prawo Kanoniczne, 2013)
The sacrament of order is not administered primarily for the personal sanctification of those who receive it, but to serve the Church as sacred minister. The Article presents the decision making process undertaken by the diocesan Bishop when deciding upon the maturity/readiness of a candidate to receive presbyter orders - from the moment he enters the Seminary till the day of receiving the sacrament. It lists documents accompanying the newly ordered presbyter and can be a help for those supporting the Bishop when deciding upon who should be promoted to the ministry of lector, acolyte and become a priest. The author focuses mostly on the legal aspect of the matter concentrating on the alumni incardinated to the diocese.